(3OjhGf GHf NaGLI GdCfOdSjs - (3GHf NaGLI , CHh ESMGb EHQGgje Hf CHj GdaJM Hf NaGLI, CHh ESMGb,J (B533 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi YR HaVdg CeG HYO aEfi cfJ hGdTHGH jQb NVGQg hjLa ZRGQg s
(3BNQgG (B:s
(3hgd ef SQhQ Ch CeGf dYGbd heaVi ZdHhQ GdZGHQjf Edi GdehJ s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B74s
Keywords: (3GdCOHs